First experiences with the Airo mobile intraoperative CT scanner in acetabular surgery—An analysis of 10 cases. Issue 2 (18th February 2019) - Keil, Holger; Beisemann, Nils; Schnetzke, Marc; Vetter, Sven Y.; Grützner, Paul A.; Franke, Jochen
Abstract: Background: Being a proven method in trauma and spine surgery, intraoperative 3D imaging (CBCT) has intrinsic deficits in difficult anatomy and with artifacts because of metal implants. The purpose of this study was to evaluate the use of intraoperative computed tomography (iCT) in acetabular surgery. Methods: Ten cases of acetabular fractures that were operated with intraoperative use of the mobile CT scanner Brainlab Airo were analyzed. Data were compared with a historical group of 17 patients. Results: Additional fluoroscopy time was 24.2 seconds (6‐91), which was significantly lower than in the control group where it was 211.4 seconds (77‐446; P  < 0.000). Operation time did not differ significantly (iCT group 196.8 min [122‐288], control group 240.8 min [71‐411], P  = 0.234). Conclusion: iCT provides images of a reliable high quality and assessability. Radiation exposure to the staff is reduced while surgery time is not altered significantly. Quality of intraoperative imaging and thus patient care can substantially improve patient outcome.